Anticoagulation Quality of Warfarin and the Role of Physician-Pharmacist Collaborative Clinics in the Treatment of Patients Receiving Warfarin: A Retrospective, Observational, Single-Center Study - Sha Qiu; Na Wang; Chi Zhang; Zhi-Chun Gu; Yan Qian (Frontiers Media S.A., 2021)
Background: The management of patients receiving warfarin is complicated. This study evaluated the anticoagulation quality of warfarin, explored potential predictors associated with poor anticoagulation quality, and elucidated the role of clinical pharmacists in the management of warfarin treatment.Methods: We retrospectively collected data on patients who either initially received warfarin or returned to warfarin after withdrawal between January 1, 2015 and January 1, 2020. The primary outcome was time in therapeutic range (TTR), and a TTR of ≥60% was considered as good anticoagulation quality. The secondary outcomes included thromboembolic and bleeding events during the follow-up. We assessed the TTR of each participant and investigated the potential predictors of poor anticoagulation quality (TTR < 60%) using logistic regression analysis. Additionally, we compared the warfarin anticoagulant quality and the incidence of clinical adverse events between atrial fibrillation patients in physician-pharmacist collaborative clinics (PPCCs) and general clinics.Results: Totally, 378 patients were included. The mean TTR of patients was 42.6 ± 29.8%, with only 32% of patients having achieved good anticoagulation quality. During a mean follow-up period of 192 ± 92 days, we found no significant differences in the incidences of thromboembolic events (5.0% vs. 5.1%, p = 0.967) and bleeding events (1.7% vs. 4.7%, p = 0.241) between patients with good and those with poor anticoagulation quality. The presence of PPCCs (odds ratio [OR]: 0.47, 95% confidence interval [CI]: 0.25-0.90, p = 0.022) was an independent protective factor of poor anticoagulation quality, while the presence of more than four comorbidities (OR: 1.98, 95% CI: 1.22-3.24, p = 0.006) and an average interval of international normalized ratio monitoring of >30 days (OR: 1.74, 95% CI: 1.10-2.76, p = 0.019) were independent risk factors of poor anticoagulation quality. Compared with atrial fibrillation patients in general clinics, patients in PPCCs were found to have a significantly increased mean TTR level (48.4% ± 25.7% vs. 38.0% ± 27.6%, p = 0.014).Conclusion: The anticoagulation quality of warfarin was relatively low at our institution. The presence of more than four comorbidities and an average interval of international normalized ratio monitoring of >30 days independently contributed to poor anticoagulation quality. Meanwhile, the use of PPCC model improved the anticoagulation quality of warfarin.